Emerging Multiple Parasite Reinfection as Neglected Tropical Disease: A Case Series - Alatas, Fatima Safira; Pratiwi, Aldisa Ayu; Kurniawan, Agnes; Pudjiadi, Antonius Hocky (Journal of Child Science, 2022)
Soil-transmitted helminth infection is endemic in Indonesia, with cases of reinfection despite individualized therapy and a mass treatment program. Three cases of multiple helminth infections were described that might be associated with chronic bloody diarrhea and stunted growth. These case series alert pediatricians that untreated helminthic infections are part of the differential diagnosis in children with gastrointestinal bleeding. Environmental surveillance should be performed in high-risk areas to prevent reinfection and growth alteration. In endemic areas, bloody diarrhea warns for an early routine fecal analysis. Correct diagnosis, prompt treatment, and source control are crucial to prevent long-term complications.
Keywords: trichuriasis; multiple helminth infections; gastrointestinal bleeding; growth faltering